2017
DOI: 10.5455/ijmsph.2017.0527323092016
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of animal bite cases in a tertiary care center of Bhopal city: A cross-sectional study

Abstract: Antarctica. [3] Its global distribution has changed little since 2011, with more than 90% of rabies deaths occurring in Africa and Asia. [4] It causes more than 59,000 fatalities per year worldwide. [5] It is estimated that the South East Asia Region accounts for approximately 45% of human deaths due to rabies in the world. [6] The situation is especially pronounced in India, which reports about 18,000 to 20,000 cases of rabies a year and about 36% of the world's deaths from the disease, with 17.4 million expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
(9 reference statements)
3
10
2
Order By: Relevance
“…In the current study, the prevalence of animal bites in urban/rural residency increased significantly over the study time period, which was 1.07 higher in urban areas than rural areas. This finding is consistent with the results of the Patel et al studies in India and Iran, respectively [27,28]. However, in some studies, the higher prevalence of animal bite cases were observed in rural areas [11,23,29].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, the prevalence of animal bites in urban/rural residency increased significantly over the study time period, which was 1.07 higher in urban areas than rural areas. This finding is consistent with the results of the Patel et al studies in India and Iran, respectively [27,28]. However, in some studies, the higher prevalence of animal bite cases were observed in rural areas [11,23,29].…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results, dogs were the most common cause for animal bite, which is similar to other studies [3,11,23,27,31,34,35]. The high prevalence of animal bite by dogs can be associated with the large number of tribes living in Kermanshah as well as the presence of stray dogs through the city.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study category II dog bite were higher. 3 Contrary to this finding category III cases reported were 89.4% by Trivedi et al and 71.50% by Patel et al 10,11 In this study, the most common place of dog bite was in the streets (33.6%) and 42.9% the bite happened at night time. This may be due to inadequate illumination.…”
Section: Discussioncontrasting
confidence: 59%